FORMULASI SIRUP DEKOKTA KERANG TUDE BOMBANG (Atactodea striata) SEBAGAI HEPATOPROTEKTOR ALAMI - Ashar, Muhammad; Pratiwi, Ines Septiani; Pratama, Andri Anugrah; Feriadi, Eva (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
The Tude Bombang clam (Atactodea striata) is a potential hepatoprotective agent due to its bioactive protein content and low fat levels, which contribute to liver protection through antioxidant activity, hepatocellular repair, and prevention of lipid accumulation in liver cells. This study aimed to formulate a decoction syrup of Tude Bombang clam and evaluate its hepatoprotective effects against paracetamol-induced hepatotoxicity in mice, as well as assess its organoleptic properties, homogeneity, and pH. The results showed that SGOT and SGPT levels in the normal control group remained stable (SGOT: 17.7–17.2 U/L; SGPT: 7.5–7.2 U/L), whereas the negative control group exhibited persistent elevations (SGOT: 374.7–373 U/L; SGPT: 97.2–95.6 U/L), confirming liver damage. The positive control (curcumin) reduced SGOT to 220.3 U/L and SGPT to 102.4 U/L. The Tude Bombang clam syrup demonstrated dose-dependent hepatoprotective effects, with the 60% concentration producing the most significant reductions in SGOT (350.9 to 288.9 U/L) and SGPT (96 to 73.6 U/L), indicating its ability to stabilize liver enzymes and mitigate hepatocellular injury. Organoleptic evaluation revealed acceptable sensory characteristics, homogeneity testing confirmed uniform dispersion without sedimentation, and the pH values (7.02–7.20) fell within the neutral range recommended for oral syrups. Overall, the Tude Bombang clam syrup exhibited favorable physical properties and hepatoprotective potential through its bioactive protein content and low fat levels, making it a promising candidate for functional hepatoprotective formulations.